Adsorpsi Ion Mn(II) Pada Zeolit yang Disintesis dari Abu Dasar Batubara Termodifikasi Ditizon - Riandy Putra (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Adsorption characteristic of Mn(II) on zeolite synthesized from bottom ash with alkaline hydrothermal conditions loaded with dithizone have been examined. The parameters studied includes effect of pH, contact time, initial concentrations and temperature of Mn(II) by batch experiments. The raw and modified samples were characterized by X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier transformation infra red (FT-IR) and Surface area analyzer (SAA) and used for the removal of Mn(II) from aqueous solution. This research shows Si and Al contents of the bottom ash analysed by XRF spectrometry dominant were used for the alkaline hydrothermal conversion of the bottom ash compounds into zeolite with range SiO2/Al2O3 ratio obtained from 1 to 5. The results of XRD and FTIR showed that the activation with reflux of bottom ash by alkali hydrothermal process can produce a material which has a similar structure zeolite (zeolite-like). Hydrothermal product consists of a mixture of zeolite (zeolite Y, zeolite Na-P and zeolite X) and sodalite crystals at temperatures of 100 °C for 24 hours. Hydrothermal product showed specific IR absorption zeolite at wavenumber 300-1250 cm-1and zeolite modified dithizone showed absorption -NH and –SH at wavenumber 1496,76 and 2461,17 cm-1. The results SAA showed that with addition dithizone lowering the specific surface area of zeolite from 160,262 m²/g to 69,609 m²/g. Results of study show that adsorption of Mn(II) reaches its maximum values at pH 6 for zeolite and pH 8 for zeolite modified dithizone, respectively. The adsorption kinetics based on the pseudo-second-order rate equation indicates that the rate limiting step involving a chemical reaction. The adsorption rate constants for zeolite synthesis -0,014g/mg.min-1and for the zeolite modified dithizone 0,0204g/mg.min-1. Based on the Langmuir equation, the maximum adsorption capacity (qmax) synthetic zeolite of 2.63x10-4mol/g and zeolite modified dhitizone 2.88x10-4mol/g. Adsorption equilibrium constant for the synthetic zeolite 0,742 mg/L and for zeolite modified dithizone 2,625 mg/L. The negative ΔH and ΔS indicate an exothermic and spontaneous process. But value of ΔG is positive, which indicates that the reaction is not spontaneous. So, adsorption using two adsorbents takes place spontaneously at a lower temperature. In general, the ability of dithizone-loaded zeolite to adsorb Mn(II) is better than does the unmodified one.